Factors Influencing Job Satisfaction in the Private Sectors among Malaysian Women - Madhavedi, Sudhakar; Yuen, Goh Pei; Hoo, Wong Chee; Annamalah, Sanmugam; Paraman, Pradeep; Pung, Ng Chee (Journal of Ecohumanism, 2024)
Job satisfaction among women in Malaysia’s private sector has been declining, yet there is limited research on the factors contributing to this trend. This study aims to explore the influence of key factors such as gender stereotypes, mentoring support, and work-life balance on the job satisfaction of women employed across various industries in private sector. A structured questionnaire was developed and administered to a sample of 385 female employees in the service sector. The survey gathered demographic information and measured levels of job satisfaction alongside the perceived impact of the identified factors. The findings of this study shed light on the complex interplay between these factors and job satisfaction, providing a nuanced understanding of the challenges faced by women in the workforce. The results offer practical recommendations for organizations seeking to improve job satisfaction among female employees by promoting workplace policies that support diversity, equity, and inclusivity. This research contributes to the growing body of literature on employment satisfaction in Malaysia’s private sector and offers a basis for future studies to further examine the unique challenges encountered by women in different occupational environments.